Writing Case Reports : A Practical Guide from Conception through Publication - Packer, Clifford D.; Berger, Gabrielle N.; Mookherjee, Somnath (Springer International Publishing : Imprint: Springer, 2017)
This book provides medical students and physicians with a practical, step-by-step guide on how to write and publish a medical case report. The case report is the traditional way for physicians to describe their unique or unusual cases to a broad audience and it plays an important role in the discovery of new diseases or syndromes, unusual manifestations of disease, important adverse drug reactions, and the generation of hypotheses for further study. This book guides readers through the process from choosing a case to report on to finding a publisher and then comment on future directions and potential new uses of case reports, including expanded computer case databases to optimize care for individual patients and new applications in medical education. Interspersed throughout the text are example case reports, many written by the authors, with commentary on their experiences working with those reports to provide context and aid readers in creating clear, concise, and useful case reports. .
Keywords: Medicine.; General practice (Medicine).; elektronické knihy; electronic books